GE_GERICHTE P/21698/2016 vom 2. August 2022 - GE Cour de justice (2022)
DÉNONCIATION CALOMNIEUSE;INSTIGATION;DISPOSITIONS PÉNALES DE LA LCR;DÉPASSEMENT(CIRCULATION);ACQUITTEMENT | CP.303; CP.24.al1; CP.251; CP.90.al2; CP.351.al1; LCR.26; LCR.35; LCR.92.al2